An IIP3 enhancement technique for CMOS active mixers with a source-degenerated transconductance stage. (April 2016) - Asghari, Meysam; Yavari, Mohammad
Abstract: In this paper, a new third-order input intercept point (IIP3) enhancement technique is introduced for CMOS active mixers with a source-degenerated transconductance stage. In the proposed technique, the third-order Volterra kernel of the output current of the transconductance stage is significantly attenuated by producing a new interaction term which is in an equal magnitude but an opposite phase related to the stage's total third-order intermodulation (IM3) current. For this end, a second-order intermodulation (IM2) current with an adjustable magnitude and phase is produced and injected to the transconductance stage. The proposed mixer has been designed for IEEE 802.11 applications with input frequency and output bandwidth equal to 2.4 GHz and 20 MHz, respectively, and simulated using a 90 nm RF-CMOS technology. Spectre-RF simulation results reveals that the IIP3 improves about 17.5 dB and 18.2 dB compared to the conventional mixers with source-degenerated and fully-differential transconductance stages, respectively, while only 1.2 mA extra current is drawn from a single 1.2 V power supply. In addition, the proposed technique has no effect on other parameters of the mixer such as the noise figure and conversion gain.